Catalytic Synthesis of Bi‐ and Teraryls in Aqueous Medium with Palladium(II) Complexes of 2‐(Pyridine‐2‐ylmethylsulfanyl)benzoic Acid. Issue 3 (18th December 2014) - Prakash, Om; Joshi, Hemant; Sharma, Kamal Nayan; Sharma, Alpesh Kumar; Singh, Ajai K.
Abstract: Suzuki–Miyaura coupling reactions of phenylboronic and 1, 4‐phenylenediboronic acid with ArBr to form bi‐ and teraryls have been efficiently catalyzed by the air‐ and moisture‐insensitive complexes [PdCl2 L1 ] [1, L1 = 2‐(pyridine‐2‐ylmethyl)sulfanylbenzoic acid; 0.05–0.5 mol‐%] and [Pd(L2 ‐H)2 ] (2, L2 ‐H = 2‐pyridin‐2‐yl‐benzo[b]thiophen‐3‐ol; 0.01–0.5 mol‐%). The complexes were formed by the reaction of [Pd(CH3 CN)2 Cl2 ] withL1, and the catalysis proceeds in water for1 . The loading of 0.1–0.5 mol‐% of Pd is very promising for the coupling reactions to form teraryls. The COOH group imparts solubility to1 in water. LigandL2 is formed by the unprecedented cyclization ofL1 in the course of the complexation reaction. The yield of2 increases with the reaction time (5 h: 70 %; 24 h: 85 %). The two complexes andL1 have been characterized by NMR spectroscopy ( 1 H and 13 C{ 1 H}). The single‐crystal structures of1 and2 have been solved, and the Pd–S, Pd–N, and Pd–O bond lengths are 2.269(2), 1.999(6)–2.057(2), and 1.9787(17) Å, respectively. Nanoparticles (NPs) with a narrow size distribution (ca. 3.0–5.5 nm for 80–85 % of the particles) formed at the start of these reactions and appear to be important for the catalytic coupling. Poisoning experiments and a two‐phase test have shown that the catalysis is largely homogeneous and involves [Pd 0 –Pd II ] processes. The bond lengths and angles calculated by DFT are consistent with the experimental ones. Abstract : Complexes [PdCl2 L1 ] [1, L1 = 2‐(pyridine‐2‐ylmethyl)sulfanylbenzoic acid] and [Pd(L2 ‐H)2 ] (2, L2 ‐H = 2‐pyridin‐2‐yl‐benzo[ b ]thiophen‐3‐ol) catalyze Suzuki coupling (1 in water) reactions to form bi‐ and teraryls.L2 forms by an unprecedented cyclization ofL1 . Pd nanoparticles (NPs) generated in situ play a role in the catalysis, which is a combination of homogeneous and heterogeneous processes.